Academic Supervision Of Madrasah Heads In Improving Teacher Performance In Karawang State Madrasah Aliyah - Siti Jaenab; Sutaryat Trisnamansyah; Sofyan Sauri; Hanafiah (CV. Inara, 2022)
Teacher performance is an important aspect of improving the quality of education in Indonesia. Academic supervision of madrasah principals is one of the functions of education management that will help teachers improve their performance on an ongoing basis. This study aims to investigate and provide an overview of improving teacher performance through the academic supervision of the madrasah principal at Madrasah Aliyah Negeri Karawang. This research is a qualitative descriptive study involving the principal, teachers, and stakeholders in data collection. Data was collected through observation, interviews, and written document studies. Data analysis uses data reduction, presentation, and leverage techniques. The results of this study indicate that the academic supervision of the head of Madrasah Aliyah Negeri Karawang is effective in improving teacher performance. The principal of the madrasah does good and systematic planning, good communication between the madrasah principal, the supervision team and the teachers so as to support harmony in achieving the goals of supervision and changes in the expected performance improvement. The example of the madrasa principal in providing instructions, motivation and coaching is a factor supporting the success of academic supervision. still teachers with performance that requires improvement, but follow-up supervision can continue to be carried out by providing opportunities for teachers to continue to improve their performance through direct coaching by the principal, being included in the evaluation of KTSP learning training, and instructed to conduct competency improvement learning through the Subject Teacher Consultation